The Retirement Consumption Puzzle Effect in Indonesia: Evidence from IFLS 4 and 5 - Putri, Margareta Vania; Sugiyanto, Catur (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: This study aims to see whether the retirement consumption puzzle occurs in Indonesia. The retirement consumption puzzle refers to when there is a decline in consumption in retirement which is not in line with the life-cycle hypothesis. Background Problems: Previous studies have revealed that consumption shifts when entering retirement due to efficient spending. This research analyzes the consumption pattern of the Indonesian elderly peculiarly in the frame of the retirement consumption puzzle. Novelty: There is a lack of studies on the effect of retirement on consumption by Indonesian retirees and prior research has focused on the impact of retirement on household expenditure. Research Methods: This study uses data from the Indonesian Family Life Survey (IFLS) wave 4 and 5 from the years 2007 and 2014. It uses panel data and the total sample is 2,556. It also uses the difference in differences (DiD) method to see whether the change in labor status toward retirement causes a decrease in consumption in households in Indonesia. Then, this study also uses the division of age categories as the robustness check. Finding/Results: The results of this study show that there is a retirement consumption puzzle in Indonesia indicated by a decrease of 19.9% in total expenditure per capita. Conclusion: The consumption decrease in retirement demonstrates that the government should consider pension funds and create social security programs to maintain the welfare of elderly people.